Factors That Motivate Students to Register for Private Tutoring Using The Factor Analysis Method - Nurhayati, Ai (Sainteks: Jurnal Sain dan Teknik, 2024)
This research aims to identify factors driving students' motivation to register for private lessons. The method used in this research is the factor analysis method with the help of statistical software. The analysis technique in this research uses Principal Component Analysis. The research results show that two main factors motivate students to register for private tutoring: the benefit and reward factors. The benefit factor comprises the variables of many assignments, the desire for further studies, and the price offered. The award factor consists of the prestige variable for achievements and Olympic competitions.